Numbered Head Together untuk Meningkatkan Kemampuan Operasi Pengurangan Anak Diskalkulia di Kelas Inklusif - Mahdi, Arisul; Yusuf, Rahmadani; Efrina, Elsa (Jurusan Pendidikan Luar Biasa Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2018)
The problem was founded at elementary school, some student’s has not been able to did subtraction. When writing, the test students’ subtracts the small numbers with the large numbers by reversing without using borrowing technique. Students’ have difficulty in solve problems about the concept of mathematical, it is give a negative impact if it is not solved. The alternatives that are done to help dyscalculia students’ one of them by apply cooperative learning numbered head together type. Cooperative learning Number Head Together (NHT) type is learning model which aims to give each students' an opportunity to express his idea without fear of wrong and increase the sense of appreciation of his friends' opinions while explaining in front of the class. With the ​numbering then the students' will have the responsibility to appear to the front of the class when the number is called.